Theoretical and experimental study on multiscale coupled Mohr–Coulomb shear strength criterion of fibre-reinforced sand - Deluan Feng; Yuxin Wang; Shihua Liang (Underground Space, 2024)
Fibre-reinforced sand (FRS) is a multiphase and multiscale geo-material, which is widely used in geotechnical engineering as supporting structure of excavation of underground space and reinforcement of foundation of underground structures, and its strength is determined by the properties of the heterogeneous substances of the FRS and their coupling mechanical responses. In order to investigate the influence of fibre characteristics and mechanical properties on the shear strength of the FRS, according to the microscopic interface slip effect generated by the interaction between sand particles and the interaction between these particles and fibre, the material phase of the FRS is divided to conceptualize a micro cell element of the FRS that is capable of reflecting the internal material characteristic information of the FRS. Moreover, based on the coordinated deformation condition between fibres and sand particles at the microscale and the couple stress theory that is capable of effectively describing the discontinuous mechanical responses at the sand-fibre interface, a mesomechanism-based multiscale Mohr–Coulomb shear strength criterion of the FRS is derived, and the yield locus of the FRS is also drawn on the π plane. Furthermore, a series of FRS samples with different fibre content and fibre length were prepared by adopting the freezing method, and consolidated and drained triaxial compression tests were conducted on these samples to validate the proposed multiscale coupled Mohr–Coulomb shear strength criterion. Results show that the multiscale coupled Mohr–Coulomb shear strength criterion is capable of effectively reproducing and predicting the yield strength of the FRS. The yield locus of the FRS extends outwards as fibre content and fibre length increase. The yield stress of the FRS predicted by the proposed multiscale coupled Mohr–Coulomb shear strength criterion is in good agreement with that of the test result.